Future of former German colonies (Colonial Letters and the Contact of Knowledges, 1921)
This file contains colonial letters on the furture of former German colonies
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies